Urgensi Bimbingan Konseling Sekolah Dasar: Pengabdian dalam Sarasehan Daring di SDN 8 Nagrikaler Purwakarta - Yubena Abigail Serewati Tambunan; Alifia Nurmaulida Subhan; Nurul Hikmah; Nihda Meiftah Farhani; Aurel Leftia Safarina; Raden Cory Nurachman Soviyana; Hisny Fajrussalam; Mamad Kasmad; Idat Muqodas (Universitas Pendidikan Indonesia Kampus Serang, 2021)
In Indonesian elementary school, it is still rare to find special guidance and counseling teachers, so that in the end, the responsibility is delegated to the classroom teacher. In fact, through the Regulation of the Minister of Education and Culture of the Republic of Indonesia number 111 of 2014, the government has stated that the elementary school level should have its own counseling guidance service. Seeing the gap and the need for these services, special discussions are needed in order to equalize perceptions and introduce effective steps for handling students' psychological problems for elementary school teachers. This is what underlies the purpose of this workshop, which is to equalize the perception of elementary school teachers regarding the importance of special counseling guidance services. Discussions about the steps for handling cases both when conventional learning and when distance learning took place were the outcomes that participants found in this online workshop. The focus of case handling in conventional learning is on sexual harassment of students while in distance learning the focus is on stress experienced by students.